Proses Audit Internal pada Sistem Produksi Panel Listrik PT. NZM - Naufal Zaki Musyaffa; Agus Bagus Budi N (Masyarakat Ekonomi Syariah Bogor, 2026)
The production system is a core activity in manufacturing companies that requires consistent control and supervision to ensure its implementation remains aligned with established plans and procedures. This study aims to examine the role of internal audit in identifying deviations within the production system of PT. NZM and to analyze the follow-up actions taken to address the audit findings. This research adopts a qualitative approach using a case study method, conducted through direct observation of production activities, interviews with relevant personnel, and a review of internal audit documents. The results indicate that internal audits not only identify procedural nonconformities but also reveal weaknesses in production control at certain stages, which affect the calculation of production costs and overall operational effectiveness. The follow-up actions, including process evaluation, the implementation of corrective and preventive measures, and the improvement of work procedures, were found to contribute positively to addressing the identified weaknesses. Therefore, internal audit plays a significant role as an effective control mechanism in enhancing the reliability of the production system and reducing operational risks within the company.